Reliability of the frontal sinus index as a maturity indicator - Ajinkya A Patil; Ameet V Revankar (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of this study was to compare the reliability of frontal sinus as a skeletal maturity indicator in males and females. Setting and Sample Population: Lateral cephalograms of 75 males and 75 females, both in pre- and post-pubertal stages of development as determined by Middle phalanx of the third finger (MP3) radiographs. Materials and Methods: Lateral cephalograms were analyzed for frontal sinus maturity. Maximum height, maximum width and height to width ratio of the sinus were calculated. The mean height to width ratio of the sinus at respective MP3 stages were tabulated and subjected to statistical analysis to determine the correlation. Correlation at different MP3 stages between males and females was also determined. Results: Statistically significant differences were observed between the mean values of F and FG along with F and I stage in males, significant difference between the values of FG stage among males and females were also observed. Conclusion: Based on statistical and direct comparison of raw data, study concludes that frontal sinus is not reliable as a sole criterion for prediction of skeletal maturity.